Nanoelectronics implementations of logic and/or with memristors / Azman Nasrudin - Nasrudin, Azman (2013)
A memristor is a two terminal passive component which is a non-linear circuit element relating to charge, q and magnetic flux linkage, ϕ [5]. This research focuses on implementing the component into hybrid electronic device that would give identical result to its identical device which is fully CMOS structured. The research include integrating spice-model of the memristor into appropriate software for simulation, analysis on particular aspects which is the speed and power dissipation and then comparing the hybrid of the CMOS and memristor to a more familiar full CMOS device. The logic AND and OR device aspects of the hybrid is similar, only the full adder output sum did not match. According to the analysis, the hybrid design would give better power dissipation and smaller layout size compared to the fully integrated CMOS design only its disadvantage is at its speed but would be solved by implementing buffer to the output, without overcompensating the size of the design.